RETRACTED: NaHS Protects against the Impairments Induced by Oxygen-Glucose Deprivation in Different Ages of Primary Hippocampal Neurons - Yu, Qian; Wang, Binrong; Zhao, Tianzhi; Zhang, Xiangnan; Tao, Lei; Shi, Jinshan; Sun, Xude; Ding, Qian (Frontiers in Cellular Neuroscience, 2017)
Brain ischemia leads to poor oxygen supply, and is one of the leading causes of brain damage and/or death. Neuroprotective agents are thus in great need for treatment purpose. Using both young and aged primary cultured hippocampal neurons as in vitro models, we investigated the effect of sodium hydrosulfide (NaHS), an exogenous donor of hydrogen sulfide (H2S), on oxygen-glucose deprivation (OGD) damaged neurons that mimick focal cerebral ischemia/reperfusion (I/R) induced brain injury. NaHS treatment (250 μM) protected both young and aged hippocampal neurons, as indicated by restoring number of primary dendrites by 43.9% and 68.7%, number of dendritic end tips by 59.8% and 101.1%, neurite length by 36.8% and 66.7%, and spine density by 38.0% and 58.5% in the OGD-damaged young and aged neurons, respectively. NaHS treatment inhibited growth associated protein 43 (GAP-43) downregulation, oxidative stress in both young and aged hippocampal neurons following OGD damage. Further studies revealed that NaHS treatment could restore ERK1/2 activation, which was inhibited by OGD-induced protein phosphatase 2 (PP2A) upregulation. Our results demonstrated that NaHS has potent protective effects against neuron injury induced by OGD in both young and aged hippocampal neurons.